The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/ana.22240
|View full text |Cite
|
Sign up to set email alerts
|

A phase 3 trial of extended release oral dalfampridine in multiple sclerosis

Abstract: This interventional study provides class 1 evidence that dalfampridine extended-release tablets produce clinically meaningful improvement in walking ability in a subset of people with MS, with the effect maintained between doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
344
5
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(383 citation statements)
references
References 20 publications
27
344
5
7
Order By: Relevance
“…In the two phase III clinical trials, a treatment with 10 mg of dalfampridine twice daily improved the walking ability measured by the timed 25 Foot Walk test (T25FW) in responders by about 25%. Responders accounted for 35–43% of the study population (Goodman et al., 2009, 2010). Nonresponders did not benefit from dalfampridine treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the two phase III clinical trials, a treatment with 10 mg of dalfampridine twice daily improved the walking ability measured by the timed 25 Foot Walk test (T25FW) in responders by about 25%. Responders accounted for 35–43% of the study population (Goodman et al., 2009, 2010). Nonresponders did not benefit from dalfampridine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent adverse events were urinary tract infections, insomnia, dizziness, nausea, and headache. Furthermore, dalfampridine might increase the risk of seizure (Goodman et al., 2009, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…This formulation is known as prolonged-, modified, or sustained release fampridine in some countries outside of the USA. Approval was based on two phase 3 clinical trials that showed an approximate mean 25% increase in walking speed among the 35–43% of patients who responded to treatment with dalfampridine-ER2,3.…”
Section: Introductionmentioning
confidence: 99%
“…This approval was based on two Phase 3 clinical trials that demonstrated a significant improvement in walking speed relative to placebo among patients who responded to treatment2,3.…”
Section: Introductionmentioning
confidence: 99%